Code division multiplexing lightwave networks based upon optical code conversion. - Kitayama, K. (IEEE Journal on selected areas in communications)
Lightwave networks realized through code division multiple access techniques are extensively studied to determine their ultimate capabilities. Here, these concepts are extended to network implementation by introducing an optical code division multiplexing (OCDM) multihop strategy using optical coding. It is shown that this approach is effective in scaling up existing wavelength division multiplexing (WDM) networks without a significant drain of the wavelength resources. The concept of a virtual optical code path (VOCP) is introduced within the transport layer of the network. It is demonstrated that this is a potential solution to wavelength path (WP) allocation problems which may plague WDM based transport networks of the future. Crucial to the VOCP concept is optical code conversion. The interplay between this added functionality and the optical cross-connect is highlighted; the optical cross-connect serves to establish VOCP/VWP (virtual wavelength path) in the hybrid transport layer. An example of optical code conversion is introduced. It is based on coherent OCDM principles in which bipolar phase-shift keyed (PSK) optical pulse sequences are used as the signature codes. Error-free code conversion using a four-chip optical encoder/decoder is successfully performed at 1.24 Gbit/s. The results show the feasibility of high bit rate OCDM transmission with optical code conversion